Economic effects of the COVID-19 pandemic on entrepreneurship and small businesses - Maksim Belitski; Christina Günther; Alexander Kritikos; Adriaan R. Thurik (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
The existential threat to small businesses, based on their crucial role in the economy, is behind the plethora of scholarly studies in 2020, the first year of the COVID-19 pandemic. Examining the 14 contributions of the special issue on the 'Economic Effects of the COVID-19 Pandemic on Entrepreneurship and Small Businesses,' the paper comprises four parts: a systematic review of the literature on the effect on entrepreneurship and small businesses; a discussion of four literature strands based on this review; an overview of the contributions in this special issue; and some ideas for post-pandemic economic research.
Keywords: L26; J38; I18; 330; Small businesses; Entrepreneurs; COVID-19 pandemic; Economic effects